The impact of energy prices on green innovation - Marius Christian Ley; Tobias Stucki; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2013)
Based on patent data and industry specific energy prices for 18 OECD countries over 30 years we investigate on an industry level the impact of energy prices on green innovation activities. Our econometric models show that energy prices and green innovation activities are positively related and that energy prices have a significantly positive impact on the share of green innovations in non-green innovations. More concretely, our main model shows that a 10% increase of the average energy prices of the previous five years results in a 2.7% and 4.5% increase of the number of green innovations and the share of green innovations in non-green innovations, respectively. We also find that the impact of energy prices increases with an increasing lag between energy prices and innovation activities. Robustness tests confirm the main results.
Keywords: O30; O34; Q55; 330; Innovation; environment; energy prices; Energiepreis; Industrielle Forschung; Nachhaltige Entwicklung; OECD-Staaten